(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
“Rape, the most basic but most serious violation of women’s human rights, is punishable by law and unanimously regarded as a heinous crime worldwide. The Supreme Court of India has stated very clearly that rape is an immortal disgrace and the most serious crime against dignity. On the other hand, marital rape is rape that takes place within the confines of the institution of marriage. This is physical abuse committed by her husband herself. Under the Indian scenario, under Section 375 of the Indian Penal Code, the rape of a woman over 15 years old is not considered a punishable offence. The disclaimer clause is not just an accidental loophole in the law, but has its roots in the English legal system which can be traced back to a judgment made nearly 300 years ago by CJ Lord Hale in the 20th century. According to the National Family Health Survey (2015), 10.4 of married women of all ages complain of domestic sexual violence. Even constructivist social theory holds that this social reality is due to men having dominated the legislative and political spheres since ancient times. The rationale for marital reluctance is the concept of irrevocable implied consent, which means in layman’s terms that once a woman is married, she has given her consent. ..